Atypical presentation of transverse myelitis in a young woman with normal imaging without sensory level: A case report (Sir Salimullah Medical College Journal, 2025)
Transverse myelitis (TM) is a spinal cord inflammatory condition that causes immediate sensory loss and motor paralysis below the lesion. The cause of the disease is diverse, and diagnosis of TM can be challenging due to the disease's low frequency and often subtle onset. We present the case of a 45-year-old female who was referred to the neurology ward with complaints of low back discomfort, urine retention, and inability to pass stool. She also complained about numbness in her inner thighs and perianal region. There were no complaints about her upper limbs. While in the neurology ward, she had left lower extremity paralysis and sensory abnormalities that gradually worsened bilaterally, eventually leading to a diagnosis of transverse myelitis. Transverse myelitis is a rare diagnosis, but it is an important clinical consideration when examining patients who arrive with pain and increasing neurologic symptoms.Sir Salimullah Med Coll J 2024; 32: 39-43